Optimalisasi Produktivitas Petani Tradisional dalam Mencapai Sustainable Development Growth di Desa Pakantan Ditinjau dari Ekonomi Islam - Aisyah Aisyah; Fauzi Arif Lubis; Rahmat Daim Harahap (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to optimize the productivity of traditional farmers in Pakantan villages and achieve sustainable growth through an Islamic economic approach. The research methods used are qualitative and based on a case study approach. Data analysis was performed using a descriptive qualitative approach and Shariah financial analysis. The results showed that there are several factors that affect the productivity of traditional farmers in Pakantan villages, including social, economic and technical factors. Sustainable development strategies, such as the use of modern agricultural techniques, the establishment of farmer cooperatives and the application of Islamic economic principles such as justice, sustainability and independence, are needed to increase farmers' productivity. The conclusion of this study is that productivity optimization of traditional farmers in Pakantan village can be achieved through an economic approach. Sustainable and eco-friendly Islam. Therefore, it is proposed that the government and communities can work together to apply Islamic economic principles to the agricultural development of Pakantan villages. Keyword: Productivity optimization, traditional farming, sustainable growth, Islamic economy